Influence of strength training background on postactivation potentiation response - Batista, M. A. B.; Roschel, H.; Barroso, R.; Urginowitsch, C.; Tricoli, V. (The Journal of Strength and Conditioning Research, 2011)
The aim of this study was to evaluate the influence of the subjects' level of maximal dynamic strength and training background on postactivation potentiation (PAP). A group of 23 subjects, composed of power track-and-field athletes (PT = 8), bodybuilders (BB = 7), and physically active subjects (PA = 8), participated in the study. Maximal dynamic strength (1 repetition maximum test) was assessed in the leg press exercise for subjects' characterization. Their countermovement vertical jump (CMJ) performance was assessed before and after 2 different conditioning activity (CA) protocols (1 or 3 maximum voluntary isometric contractions [MVICs] of 5-second duration in the leg press exercise) or after control (no CA), performed on separate days. No significant differences among groups were found for CMJ height or take-off velocity after any of the CA protocols (p < 0.05). However, individual analysis showed that some subjects increased performance in response to the CA, despite their previous training history. We concluded that subjects' level of maximal dynamic strength and training background have no influence on PAP manifestation. Our data suggest that coaches should individually identify the athletes that are PAP responders before introducing MVICs as part of their warm-up routines.